12d+3=-2d+17

Simple and best practice solution for 12d+3=-2d+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12d+3=-2d+17 equation:


Simplifying
12d + 3 = -2d + 17

Reorder the terms:
3 + 12d = -2d + 17

Reorder the terms:
3 + 12d = 17 + -2d

Solving
3 + 12d = 17 + -2d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '2d' to each side of the equation.
3 + 12d + 2d = 17 + -2d + 2d

Combine like terms: 12d + 2d = 14d
3 + 14d = 17 + -2d + 2d

Combine like terms: -2d + 2d = 0
3 + 14d = 17 + 0
3 + 14d = 17

Add '-3' to each side of the equation.
3 + -3 + 14d = 17 + -3

Combine like terms: 3 + -3 = 0
0 + 14d = 17 + -3
14d = 17 + -3

Combine like terms: 17 + -3 = 14
14d = 14

Divide each side by '14'.
d = 1

Simplifying
d = 1

See similar equations:

| 16=x+6 | | 12x-83+6x=121 | | 6(1-8n)-11n=6(n+1)-10n | | -8(1+n)=-(6n-4) | | -11=n-10 | | -3(2-a)=9(2a+6) | | -17p=51 | | 6(-10+5x)=-4(-7-2x) | | 87=3x+6 | | 4x+9=8+x | | 3+6x+9=6x+7-8 | | 4y^2-16y+1=0 | | -8=x-10 | | -6(11m-6)=-9m-6(10m-4) | | 7x+3(x-8)=4(y+2)-3 | | -8(11-9x)+1=2(8-12x)-7x | | 9.46+30x=15.3 | | y=1-9x | | 20*x=240 | | y^4+6y^3+17y^2+22y+14=0 | | n+17=23 | | 2a^3-a^2+a-2=0 | | .5*-2= | | 1=x-11 | | .5*-2+6=-7 | | 2a^4+a^3+4a^2+a+2=0 | | q^2-11q+18=0 | | 1-12b-7+8b=-4(b-3)-3(9-b) | | -143=-13x | | 1-12b-7+8b=-4(b-3) | | (4+3)+.70x=24.50 | | 0.7x-3.2=1.7 |

Equations solver categories